2013
DOI: 10.3727/096368912x657387
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine TGF-β Induces Epithelial to Mesenchymal Transition in Human Amniotic Epithelial Cells

Abstract: Human amniotic epithelial cells (hAECs) have been the object of intense research due to their potential therapeutic use. In this paper, we present molecular evidence of a bona fide epithelial to mesenchymal transition (EMT) undergone by hAECs. Amniotic membrane (AM)-derived hAECs showed the presence of typical epithelial markers such as E-cadherin and cytokeratins. hAECs in culture, however, underwent morphological changes acquiring a mesenchymal shape. Epithelial cell markers were lost and typical mesenchymal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 47 publications
2
55
0
1
Order By: Relevance
“…Consequently, as the results related above indicate the participation of TGF‐ß signalling in the promotion of HaCaT cell migration by AM, we performed assays to determine the involvement of either the canonical or the non‐canonical TGF‐ß signalling in this process. Engagingly, the application in scratch cultures of a neutralizing antibody for all TGF‐ß isoforms (Alcaraz et al, ) reported similar effects over AM‐induced as well as TGF‐ß‐induced cell migration than using TGFRi (Figure c), thus pointing at canonical signalling as the driver for the observed TGF‐ß promotion for cell migration.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Consequently, as the results related above indicate the participation of TGF‐ß signalling in the promotion of HaCaT cell migration by AM, we performed assays to determine the involvement of either the canonical or the non‐canonical TGF‐ß signalling in this process. Engagingly, the application in scratch cultures of a neutralizing antibody for all TGF‐ß isoforms (Alcaraz et al, ) reported similar effects over AM‐induced as well as TGF‐ß‐induced cell migration than using TGFRi (Figure c), thus pointing at canonical signalling as the driver for the observed TGF‐ß promotion for cell migration.…”
Section: Resultsmentioning
confidence: 88%
“…Regarding cytokines, from the many involved in wound healing, TGF‐ß is considered to play a prominent role in the process, as it is known to stimulate fibroblast recruitment and to watch over epithelium to mesenchyme transition of keratinocytes, thus determining their migratory and proliferation status (Davies et al, ; Massague, ). Noteworthy, AM is known to secrete EGF, keratinocyte growth factor and hepatic growth factor, as well as relevant levels of TGF‐ß (Alcaraz et al, ; Koizumi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although samples initially consisted of a mixture of epithelial and mesenchymal-stromal cells, enrichment of the mesenchymal population occurred after their expansion in culture. This could be due to the previously described epithelial-to-mesenchymal cell transition that amniotic epithelial cells undergo after various passages in culture (37). Both in vitro and in vivo studies have demonstrated that cells from either the epithelial or mesenchymal layers exert immunomodulatory properties and ameliorate disease with inflammatory bases, including lung and liver fibrosis and EAE (15,19,(38)(39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…38 TGFβ is produced in fetal membrane cells in response to CSE treatment and oxidative stress and it is a well-known activator of epithelial mesenchymal transition (EMT). 7577 EMT is an inflammatory state 78 and Chaudhuri et al has shown fetal membrane EMT occurring at term. 79 Similar findings were reported by Mogami H et al in fetal membranes rupture models.…”
Section: Commentmentioning
confidence: 99%